Diseño arquitectónico de un centro de salud mental, considerando concepto de Passive House en la ciudad de Guayaquil - Salazar Gutiérrez, Alex Enrique (2024)
Mental health is a pivotal subject in Ecuador, with a prevalence of disorders at 25.2% among adults. Recreational mental health centers offer an effective alternative by combining playful activities with mental health services in a positive and stimulating environment. This project proposes a center of this kind in Guayaquil, located in Kennedy Norte, an area with a high incidence of mental disorders, especially among the neurodivergent population.....